1986
DOI: 10.1126/science.232.4758.1625
|View full text |Cite
|
Sign up to set email alerts
|

Floral Evolution: Attractiveness to Pollinators Increases Male Fitness

Abstract: Because availability of resources often limits seed or fruit set, increased visits by pollinators may not always lead to increases in maternal reproduction. This observation has led evolutionary biologists to hypothesize that a plant's ability to attract pollinators may have its primary impact on male fitness achieved through the fertlization of ovules. This interpretation of angiosperm reproductive ecology is supported by field experiments. Pollinating insects strongly discriminated between two Mendelian peta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
266
2
9

Year Published

1988
1988
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(286 citation statements)
references
References 28 publications
9
266
2
9
Order By: Relevance
“…In a hand-pollination experiment, fruit set of wild radish increased with receipt of supplemental pollen, but seed set did not (Pfennig and Conner 1997). Stanton et al (1986) found that while colour discrimination by pollinators had no significant effect on relative maternal function (fruit and seed production), yellow-coloured flowers were much more successful as pollen donors.…”
Section: Reproductionmentioning
confidence: 99%
“…In a hand-pollination experiment, fruit set of wild radish increased with receipt of supplemental pollen, but seed set did not (Pfennig and Conner 1997). Stanton et al (1986) found that while colour discrimination by pollinators had no significant effect on relative maternal function (fruit and seed production), yellow-coloured flowers were much more successful as pollen donors.…”
Section: Reproductionmentioning
confidence: 99%
“…Thus a potential caveat for the interpretation of results is that both phenotypic markers and isozymes have potential limitations, due to the fact that the markers themselves may directly affect paternity success. For instance, in Raphanus raphanistrum, pollinators preferentially visit the yellow petal-colour morph over white-petal flowers (Stanton et al 1986). Similar effects can occur for different alleles at isozyme loci, that can affect paternity, via linked loci or directly (Travers & Holtsford 2000;Travers & Mazer 2001).…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Heritable markers include phenotypic markers with a mendelian genetic basis, such as flower and leaf colour (e.g. Stanton et al 1986;Snow & Mazer 1988;Cowan et al 2000), allozymes and other molecular markers. To date, it is isozyme electrophoresis that still makes the major methodological contribution to the body of published studies on paternity shares within fruits in plants (Table 1).…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Waser & Price, 1983 ;Stanton, Snow & Handel, 1986 ;Nilsson, 1988 ;Campbell et al, 1991, Campbell, Waser & Price, 1996. Pollinator choice is determined by the presence of rewards (e.g.…”
Section: Pollinator-mediated Selectionmentioning
confidence: 99%